Spectrophotometric Determination of Iron(II) after Solid Phase Extraction of Its 2,2′ Bipyridine Complex on Silica Gel-Polyethylene Glycol - Nahid Pourreza; Saadat Rastegarzadeh; Ali Reza Kiasat; Hossein Yahyavi (Journal of Spectroscopy)
A new solid phase extraction procedure was developed for preconcentration of iron(II) using silica gel-polyethylene glycol (silica-PEG) as an adsorbent. The method is based on retention of iron(II) as 2,2′ bipyridine complex on silica-PEG. The retained complex is eluted by 1.0 mol L−1 of sulfuric acid-acetone mixture (1:2) and its absorbance is measured at 518 nm, spectrophotometrically. The effects of different parameters such as pH, concentration of the reagent, eluting reagent, sample volume, amount of adsorbent, and interfering ions were investigated. The calibration graph was linear in the range of 1–60 ng mL−1 of iron(II). The limit of detection based on 3Sb was 0.57 ng mL−1 and relative standard deviations (R.S.D) for ten replicate measurements of 12 and 42 ng mL−1 of iron(II) were 2.4 and 1.7%, respectively. The method was applied to the determination of of iron(II) in water, multivitamin tablet, and spinach samples.